Inflation and Unemployment Relationship in Türkiye: An Analysis within the Framework of the Phillips Curve (Horizon Multidisciplinary Scientific Journal, 2026)
Purpose: This study aims to examine the long-term relationship between annual inflation rates and unemployment rates in the Turkish economy over the 64-year period from 1960 to 2023 within the theoretical framework of the Phillips Curve.Method: A quantitative research method was adopted, utilizing annual data obtained from the Turkish Statistical Institute (TÜİK) and the World Bank. The normality assumption of the dataset was tested using the Shapiro-Wilk test, while the existence of a linear relationship was examined through Pearson correlation analysis. In the simple linear regression model estimated by the Ordinary Least Squares (OLS) method, t-statistics and p-values were calculated, and the Gauss-Markov assumptions of the model (linearity, zero conditional mean, homoscedasticity, and absence of autocorrelation) were systematically tested. Additionally, separate analyses were conducted for three sub-periods: 1960-1979, 1980-2001, and 2002-2023.Findings: For the entire period, the Pearson correlation coefficient indicated a statistically significant, moderately positive relationship between inflation and unemployment. Although the OLS regression model produced a significant slope coefficient, its explanatory power remained low. Sub-period analyses revealed that the direction and strength of the relationship varied considerably across different economic regimes.Conclusion: The findings suggest that the traditional Phillips Curve relationship does not hold in Turkey over the long-term 64-year period. Instead, a positive correlation pattern appears to dominate, driven by stagflation dynamics, chronic inflation inertia, and external shocks. These results highlight the need for developing macroeconomic models tailored to developing economies and
Keywords: Inflation; Unemployment; Phillips Curve; Correlation Analysis; OLS Regression; Turkish Economy